Competitive Strategy in Managing Café Djayataruna Business, Natar District, South Lampung Regency - Fadillah, Dwi Fani; Purnomo, Agus (Journal of Business and Halal Industry, 2025)
As people increasingly seek spaces that offer both food and relaxation, cafes and recreational venues are gaining popularity. This study examines the marketing strategies employed by Café Djayataruna, focusing on its marketing mix. Through a qualitative case study, the research involved interviews with the owner, employees, and customers, alongside observations of the café’s operations. The findings reveal the café’s strengths, such as its diverse menu, unique experience, and strong social media presence. A SWOT analysis shows promising opportunities for growth, including food delivery services and local collaborations. However, challenges like operational inefficiencies and limited market reach need attention. The study concludes that by focusing on innovation and customer satisfaction, Café Djayataruna can strengthen its competitive position and ensure long-term success.